Ampsbeharting, ampsbediening en ampsgeborgenheid: Enkele perspektiewe op H.G. Stoker se regsbeskouing - Raath, A. W. G. (Koers, 1983)
Stokers’s inquiry into the jural realm, i.e. into human rights, jurial norms and the jural order, in relation to the divinely ordained, status or office of man in cosmic reality, is subjected to a critical evaluation. According to Stoker this status pertains to both individuals and social bodies and their mutual relatedness. Stoker’s views on administration-in-oflice are briefly compared to L. M. du Plessis's views on the law as security-in-office. Furthermore Stoker’s approach of the jural realm according to the order of creation as well as to the order of the fall of man is critically evaluated in the light of criticism From the ranks of the Philosophy of the Cosmonomic Law Idea. Such an analysis highlight the perspectives opened up by Stoker’s views on the nature of the law.